ANALISIS SISTEM INFORMASI AKUNTANSI PENGELUARAN KAS PADA PT. PLN (PERSERO) RAYON KARIANGO KABUPATEN PINRANG - Arfianty, Arfianty (Economos : Jurnal Ekonomi dan Bisnis, 2020)
Research Objectives to find out the Accounting Information System for Cash Expenditures at PT. PLN (Persero) Rayon Kariango in Pinrang Regency. This study uses a qualitative research method, namely data obtained from the results of several sources in the form of information both oral and written at the research site or with literature studies. Research data collection methods, namely observation (observation), interview (interview), and documentation. The data analysis technique used is comparative descriptive. The results showed that the accounting information system for cash disbursement at PT. PLN (Persero) Rayon Kariango in Pinrang Regency complies with the standard or procedure for applying the cash disbursement accounting information system.